Problematika Pembelajaran Daring di Madrasah Ibtidaiyah Negeri 3 Magetan - Moh Irmawan Jauhari; Suprih Hartanto; Mudzakkir Mudzakkir (Academia Publication, 2021)
Online learning is the answer to the Covid-19 pandemic that has hit all corners of the world. Face-to-face learning experiences a shift and of course this has a direct relationship with several learning components. Madrasah Ibtidaiyah Negeri 3 Magetan is one of the favorite educational institutions in Magetan with more than a thousand students. This condition in online learning certainly requires good preparation so that learning material is still conveyed. The research approach in this article is a qualitative and case study type. Snowball sampling was used to extract data from several informants. And the researcher will follow the main informant's directions who appoint other informants. Data analysis used is Miles B. Huberman's theory where there are three data analysis workflows in interrelated steps, data condensation, data presentation and drawing conclusions/verification. The results of the study stated, in online learning, teachers at MIN 3 Magetan prepared everything well considering that online learning has several weaknesses and is different from in the classroom learning. Four teacher competencies are very supportive online learning implementation considering that good skills are needed from the teacher in managing and connecting several things related to online learning. In addition, teachers are required to supervise their students with the help of parents and guardians. Evaluation or assessment in online learning is carried out by the teacher based on the quantitative and qualitative descriptions. Learning assessment that touches the psychomotor realm in online learning only touches cognitive and affective aspects.